2022
DOI: 10.3389/fimmu.2022.1054147
|View full text |Cite
|
Sign up to set email alerts
|

Pilot genome-wide association study of antibody response to inactivated SARS-CoV-2 vaccines

Abstract: Vaccines are a key weapon against the COVID-19 pandemic caused by SARS-CoV-2. However, there are inter-individual differences in immune response to SARS-CoV-2 vaccines and genetic contributions to these differences have barely been investigated. Here, we performed genome-wide association study (GWAS) of antibody levels in 168 inactivated SARS-CoV-2 vaccine recipients. A total of 177 SNPs, corresponding to 41 independent loci, were identified to be associated with IgG, total antibodies or neutral antibodies. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Analysis of the impact of host genetic variation on SARS-CoV-2 vaccine-induced immunity has found associations between variant HLA alleles and variation in vaccine-induced antibody responses, vaccine breakthrough and vaccine side effects [ 63 , 64 ]. Small-scale pilot studies have also identified loci associated with variation in antibody responses following vaccination with an inactivated vaccine [ 65 ]. Our results, showing a significantly heritable response to both vaccine efficacy and reduced disease post challenge, suggest that the DO and related mouse populations can be used to complement human studies to understand the role of genetic variation in regulating vaccine responses.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the impact of host genetic variation on SARS-CoV-2 vaccine-induced immunity has found associations between variant HLA alleles and variation in vaccine-induced antibody responses, vaccine breakthrough and vaccine side effects [ 63 , 64 ]. Small-scale pilot studies have also identified loci associated with variation in antibody responses following vaccination with an inactivated vaccine [ 65 ]. Our results, showing a significantly heritable response to both vaccine efficacy and reduced disease post challenge, suggest that the DO and related mouse populations can be used to complement human studies to understand the role of genetic variation in regulating vaccine responses.…”
Section: Discussionmentioning
confidence: 99%
“…These include MBL2 [32], ADAMTS13 [33], F8 [34] and PDGFRL [34], which are involved in clotting and have also been observed to be associated with acute Covid-19 severity. Our search reveals limited GWAS studies of long covid [35,36] or Covid-19 vaccine adverse events [37], though GWAS studies of SARS-CoV-2 vaccine antibody responses have been performed [38,39] and several mechanistic factors behind the differential vaccine response are identified [40]. Genetic correlates of vaccine adverse reactions have been studied in the context of Hepatitis B, measles, rubella, and other vaccines [41].…”
Section: Variation In Cell Uptake and Biodistributionmentioning
confidence: 99%